An example of reliability testing and establishing performance profiles for non-parametric data from performance analysis - Hughes, M.; Cooper, S. M.; Nevill, A.; Brown, S. (International Journal of Computer Science in Sport, 2003)
Recent research has proposed a simple empirical way of examining the variance of the means of performance indicators as they approach their final stability values, as more and more performances are analysed. This research aims to provide practical insight into the issues associated with establishing reliability studies, and also examining whether normative profiles of performance indicators have been established, in performance analysis, by using a practical example from recent a recent analysis project of the World Cup for association football.